Neuroblastoma - Chung, Christine; Boterberg, Tom; Lucas, John; Panoff, Joseph; Valteau‐Couanet, Dominique; Hero, Barbara; Bagatell, Rochelle; Hill‐Kayser, Christine E. (Pediatric blood & cancer, 2021)
The survival of patients with high‐risk neuroblastoma has improved significantly with the use of intensive multimodality treatment regimens, including chemotherapy, surgery, radiation therapy, myeloablative chemotherapy followed by stem cell rescue, and immunotherapy. This report summarizes the current treatment strategies used in the COG and SIOP for children with neuroblastoma. The improved global collaboration and the adoption of a uniform International Neuroblastoma Risk Group Staging System will help facilitate comparison of homogeneous pretreatment cohorts across clinical trials. Future research strategies regarding the indications for and dosages of radiation therapy to the primary and metastatic sites, and the integration of meta‐iodobenzyl guanidine therapy into the multimodal treatment program, are discussed.